Minimum 2-Year Outcomes of All-Arthroscopic Capsular Autograft Labral Reconstruction. Issue 7 (30th July 2021) - Kucharik, Michael; Abraham, Paul; Nazal, Mark; Varady, Nathan; Meek, Wendy; Martin, Scott
Objectives: Acetabular labral tears distort the architecture of the hip and result in accelerated osteoarthritis and increases in femoroacetabular stress. Uncomplicated tears with preserved, native fibers can be fixed to acetabular bone using labral repair techniques, which have shown improved outcomes when compared to the previous gold standard, labral debridement and resection. If the tear is complex or the labrum is hypoplastic, labral reconstruction techniques can be utilized to add grafted tissue to existing, structurally intact tissue or completely replace a deficient labrum. The ultimate goal is to reconstruct the labrum to restore the labral seal and hip biomechanics. Clinical outcomes using autografts and allografts from multiple sources for segmental and whole labral reconstruction have been reported as successful. However, reconstruction using autografts has been associated with substantial donor-site morbidity. More recently, all-arthroscopic capsular autograft labral reconstruction has been proposed as a way to repair complex or irreparable tears without the downside of donor-site morbidity. Since all-arthroscopic capsular autograft labral reconstruction is a novel technique, there is limited data in the literature on patient outcomes. The purpose of this study is to report outcomes in patients who have undergone this procedure at a minimum 2-year follow-up. Methods: This is a retrospective case series of prospectively collected data on patients who underwent arthroscopic acetabular labral repair by a senior surgeon between December 2013 and May 2017. Patients who failed at least 3 months of conservative therapy and had a symptomatic labral tear on magnetic resonance angiography (MRA) were designated for hip arthroscopy. The inclusion criteria for this study were adult patients age 18 or older who underwent arthroscopic labral repair with capsular autograft labral reconstruction and completion of a minimum 2-year follow-up. Intraoperatively, these patients were found to have a labrum with hypoplastic tissue (width < 5 mm), complex tearing, or frank degeneration of native tissue. Patients with lateral center edge angle (LCEA) ≤ 20° were excluded from analysis. Using the patients' clinical visit notes with detailed history and physical exam findings, demographic and descriptive data were collected, including age, sex, laterality, body mass index (BMI), and Tönnis grade to evaluate osteoarthritis. Patients completed patient-reported outcome measures and postoperatively at 3 months, 6 months, 12 months, and annually thereafter. Results: A total of 72 hips (69 patients) met inclusion criteria. No patients were excluded. The cohort consisted of 37 (51.4%) male and 35 (48.6%) female patients. The minimum follow-up was 24 months, with an average follow-up of 30.3 ± 13.2 months (range, 24-60). The mean patient age was 44.0 ± 10.4 years (range 21-64), with mean body mass index of 26.3 ± 4.3. The cohort consisted of 6 (8.3%) Tönnis grade 0, 48 (66.7%) Tönnis grade 1, and 18 (25.0%) Tönnis grade 2. Two (2.8%) progressed to total hip arthroplasty. Intraoperatively, 5 (6.9%) patients were classified as Outerbridge I, 14 (19.4%) Outerbridge II, 45 (62.5%) Outerbridge III, and 8 (11.1%) Outerbridge IV. Seventy-two (100.0%) patients had a confirmed labral tear, 34 (47.2%) isolated pincer lesion, 4 (5.6%) isolated CAM lesion, and 27 (37.5%) had both a pincer and CAM lesion. The mean of differences between preoperative and 24-month postoperative follow-up PROMs was 22.5 for mHHS, 17.4 for HOS-ADL, 32.7 for HOS-Sport, 22.9 for NAHS, 33.9 for iHOT-33.(Figure 1) The mean of differences between preoperative and final post-operative follow-up PROMs was 22.1 for mHHS, 17.6 for HOS-ADL, 33.2 for HOS-Sport, 23.3 for NAHS, and 34.2 for iHOT-33.(Table 1) Patient age and presence of femoroacetabular impingement were independently predictive of higher postoperative PROM improvements at final follow-up, whereas Tönnis grade was not.(Table 2) The proportion of patients to achieve the minimally clinically important difference (MCID), substantial clinical benefit (SCB), and patient acceptable symptom state (PASS) thresholds were also calculated.(Table 3) Conclusions: In this study of 72 hips undergoing arthroscopic labral repair with capsular autograft labral reconstruction, we found excellent outcomes that exceeded the MCID thresholds in the majority of patients at an average 30.3 months follow-up. When compared to capsular reconstruction from autografts and allografts, this technique offers the potential advantages of minimized donor-site morbidity and fewer complications, respectively. :